THE MAIN CHARACTER’S IDENTITY IN HIROMI’S HAND BY LYNNE BARASCH - Wulansari, Novika; Wiwoho, Gurendi (LINGUAMEDIA Journal, 2023)
ABSTRACT The research entitled " The Main Character`s Identity in Hiromi's Hand by Lynne Barasch." The main reason the writer chose this topic is that the main character of picture books has serious identity problems. In particular, Hiromi wants to know more about her own identity as a descendant of Japanese-American immigrants. What makes Hiromi unique is that she was born and raised when her parents immigrated to the United States of America, so despite being of immigrant descent, she has been automatically in the American environment since childhood. Hiromi's first problems involved the process by which immigrant children making the transition, making the connection, and becoming American. The writer uses the identity theory of (FU, Lamme, & Lowery, 2004); (Serpe & Stets, 2016), starting that the second problems are internal issues such as thoughts, feelings, and emotions, and external issues are social problems. The objectives of the study to examine this problem is to describe the process of identity that Hiromi experienced so that she become American and to explain how Hiromi solved the identity problem. The method use in this research is descriptive qualitative and uses a mimetic approach. The source of the data is Hiromi's picture book, and the data use the text and pictures in the picture book. As a result, it is revealed that Hiromi has a dual identity as a Japanese American girl. Hiromi is physically of Japanese descent but socially American, Hiromi eventually becomes comfortable and prefers being American. Keywords: Picture book, Identity, Multicultural literature, Asian-American immigrant, American and Japanese Culture